Lidocaine Nebulization Compared to Lidocaine Spray in Decreasing Pain, Cough and Breathless in Flexible Fiber Optic Bronchoscopy - Vita Ovaria; Yusup Subagio Sutanto; Ahmad Farih Raharjo (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2022)
Background: Flexible optical fiber bronchoscopy (FFB) is a visual airway tract examination for diagnostic and therapeutic purposes. This procedure often causes discomfort for patients, such as cough, breathlessness and pain. Lidocaine is a topical anesthetic premedication used in bronchoscopy. This study compared the use of lidocaine nebulization and lidocaine spray in inhibiting pain, cough and breathlessness in complexity of flexible fiber optic bronchoscopy.Methods: Pretest and posttest control group clinical study was conducted in patients prior to bronchoscopy at RSUD Dr. Moewardi from February to March 2020. The samples were taken by consecutive sampling technique, then randomly assigned into either lidocaine spray or nebulization. Cough and pain were assessed with VAS score while breathlessness was assessed with Borg score. The data were analyzed statically by using Chi-square test with P<0.05 was considered significantResults: Cough scores were -17.78±11.66 for nebulization and -8.33±6.18 for spray (P=0.005). Pain score were -16.67±11.38 and -9.44±7.25 for nebulization and spray respectively (P=0.045). Borg score obtained the scores for nebulization and 0.06±0.42 for spray (P=1.000).Conclusion: Both lidocaine nebulization and spray were effective in decreasing breathlessness during bronchoscopy. However, lidocaine nebulization was more effective in decreasing cough and pain.